2020
DOI: 10.1177/0963689720931435
|View full text |Cite
|
Sign up to set email alerts
|

Ganoderma lucidum Polysaccharide Enzymatic Hydrolysate Suppresses the Growth of Human Colon Cancer Cells via Inducing Apoptosis

Abstract: Ganoderma lucidum is a popular traditional Chinese medicine used in China to improve health. Previous researches have revealed that the polysaccharide from G. lucidum could exert diversity activities, including immunomodulation, antioxidant, and antitumor effects. However, the effect of enzymatically hydrolyzed G. lucidum polysaccharide (EGLP) in colorectal cancer (CRC) progression remains unknown. The present research aimed to investigate the antitumor mechanism of EGLP in human colon cancer cells. For this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Several literature reports reported that Ganoderma lucidum extract could directly inhibit tumors in nude mice with T cell deficiency: The triterpenoids derived from ethanol extracts of sporoderm-broken spores of G. lucidum effectively suppressed CRC carcinogenesis by inducing apoptosis, inhibiting migration through downregulation of MMP-1 and MMP-2, upregulating E-cadherin expression, and promoting cell cycle arrest at the G0/G1 phase; 33 Ganoderma lucidum polysaccharides inhibited autophagic flux and led to apoptosis of tumor cells (HCT116) via MAPK/ERK activation; 4 Enzymatically hydrolyzed G. lucidum polysaccharide can potentially induce apoptosis in HCT-116 human colon cancer cells by upregulating phospho-extracellular regulated protein kinases (P-ERK), cleaved caspase-3 expression, and BCL-2 associated X protein (Bax), while downregulating cyclo-oxygenase 2 (COX-2), phospho-serine/ threonine kinase 1 (p-Akt1), and B-cell lymphoma-2 (Bcl-2) expression. 34 These differences may be due to differences in the dose of GLP, tumor cell origin, and mouse models. This also suggests that the inhibitory effect of GLP on tumor cells may require a longer treatment time to be achieved, and in the early stages of treatment, T-cell immunity plays a role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several literature reports reported that Ganoderma lucidum extract could directly inhibit tumors in nude mice with T cell deficiency: The triterpenoids derived from ethanol extracts of sporoderm-broken spores of G. lucidum effectively suppressed CRC carcinogenesis by inducing apoptosis, inhibiting migration through downregulation of MMP-1 and MMP-2, upregulating E-cadherin expression, and promoting cell cycle arrest at the G0/G1 phase; 33 Ganoderma lucidum polysaccharides inhibited autophagic flux and led to apoptosis of tumor cells (HCT116) via MAPK/ERK activation; 4 Enzymatically hydrolyzed G. lucidum polysaccharide can potentially induce apoptosis in HCT-116 human colon cancer cells by upregulating phospho-extracellular regulated protein kinases (P-ERK), cleaved caspase-3 expression, and BCL-2 associated X protein (Bax), while downregulating cyclo-oxygenase 2 (COX-2), phospho-serine/ threonine kinase 1 (p-Akt1), and B-cell lymphoma-2 (Bcl-2) expression. 34 These differences may be due to differences in the dose of GLP, tumor cell origin, and mouse models. This also suggests that the inhibitory effect of GLP on tumor cells may require a longer treatment time to be achieved, and in the early stages of treatment, T-cell immunity plays a role.…”
Section: Discussionmentioning
confidence: 99%
“…lucidum effectively suppressed CRC carcinogenesis by inducing apoptosis, inhibiting migration through downregulation of MMP-1 and MMP-2, upregulating E-cadherin expression, and promoting cell cycle arrest at the G0/G1 phase; Ganoderma lucidum polysaccharides inhibited autophagic flux and led to apoptosis of tumor cells (HCT116) via MAPK/ERK activation; Enzymatically hydrolyzed G. lucidum polysaccharide can potentially induce apoptosis in HCT-116 human colon cancer cells by upregulating phospho-extracellular regulated protein kinases (P-ERK), cleaved caspase-3 expression, and BCL-2 associated X protein (Bax), while downregulating cyclo-oxygenase 2 (COX-2), phospho-serine/threonine kinase 1 (p-Akt1), and B-cell lymphoma-2 (Bcl-2) expression . These differences may be due to differences in the dose of GLP, tumor cell origin, and mouse models.…”
Section: Discussionmentioning
confidence: 99%
“…However, how GLP5 induces the changes of expression of these apoptosis-related genes needs to be further elucidated. In human colon cancer, polysaccharide hydrolysate derived from G. lucidum could induce apoptosis to suppress the growth of cells by upregulating Bax, phospho-extracellular regulated protein kinases (P-ERK), and cleaved caspase-3 and downregulating Bcl-2, phospho-serine/threonine kinase 1 (p-Akt1), and cyclo-oxygenase-2 (COX-2) (Bai et al, 2020). On other hand, polysaccharide extracted from G. lucidum may enhance the activity of NK cells to activate DNAX-associated protein 10/phosphoinositide 3-kinase/extracellular regulated protein kinases to mediate its cytotoxicity (Yang.…”
Section: Discussionmentioning
confidence: 99%
“…GLP might severe as a potential chemotherapeutic agent for the treatment of cancer with mutant p53. Enzymatically hydrolyzed GLP (EGLP) showed cytotoxic activities against CRC cells ( Bai et al, 2020 ). EGLP enhanced CRC cell apoptosis by upregulating Bax, p-ERK and cleaved caspase-3 and downregulating Bcl-2, phosphorylated Akt1 (p-Akt1) and cyclooxygenase-2 (COX-2).…”
Section: The Antitumor Activities Of Polysaccharides From G...mentioning
confidence: 99%